Colonic intussusception in the adult - Sierra, Atanasio Jorge (Cirugía del Uruguay, 2020)
Two new cases of íleo-cecal invagination in the adult are reported upon. Following a discussion of their clinical features, a brief survey of keys to diagnosis and treatement is presented.